hiV screening of migrants in the autonomous Province of Trento (North-Eastern italy) - Lanzafame, Massimiliano; Mori, Giovanni; Lattuada, Emanuela; Visentin, Donatella; Carraro, Luisa; Gargano, Roberta; Eatehmoghadam, Pirous; Zuccali, Maria Grazia (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Migrants have accounted for more than 40% of new HIV diagnoses in Europe in 2022. Among the population of asylum seekers currently present in the Trento Province, screening for HIV infection is poorly carried out for various reasons. Here we report our experience about screening for HIV infection in asylum seekers present in that area using rapid self HIV-testing.